The Gulf Cooperation Council countries – economic structures, recent developments and role in the global economy - Michael Sturm; Jan Strasky; Petra Adolf; Dominik Peschel (European Central Bank (ECB), 2008)
In the wake of high and rising oil prices since 2003, the member states of the Gulf Cooperation Council (GCC) have seen dynamic economic development, enhancing their role in the global economy as investors and trade partners. Real GDP growth has been buoyant, with non-oil activity expanding faster than oil GDP. Macroeconomic developments have also been characterised by large fiscal and current account surpluses as a result of rising oil revenues, notwithstanding fiscal expansion and rapid import growth. The most significant macroeconomic challenge faced by GCC countries is rising inflation in an environment in which the contribution of monetary policy to containing inflationary pressure is constrained by the exchange rate regimes. The overall favourable macroeconomic backdrop of recent years has provided GCC countries with an opportunity to tackle long-standing structural challenges, such as the diversification of oil-centred economies and reform of the labour markets. In a global context, apart from developing into a pole of global economic growth, GCC countries – together with other oil-exporting countries – have become a major net supplier of capital in global markets, second only to East Asia. As a result, they have become part of the international policy debate on global imbalances. Furthermore, GCC countries are home to some of the world's largest sovereign wealth funds, which raises several financial stability issues. Their role as trade partners has also increased, with the European Union being the only major region in the world maintaining a significant surplus in bilateral trade with the GCC. GCC countries are also key players in global energy markets in terms of production, exports and the availability of spare capacity. Their role is likely to become even more pivotal in the future as they command vast oil and gas reserves and benefit from relatively low costs in exploiting oil reserves.
Keywords: F40; F30; F14; E60; N15; O53; Q40; 330; Gulf Cooperation Council; global imbalances; sovereign wealth funds; financial stability; oil markets.; Nationaleinkommen; Wirtschaftswachstum; Strukturwandel; Staatsfonds; Ölmarkt; Arabische Golf-Staaten